2019
DOI: 10.1242/jcs.229534
|View full text |Cite
|
Sign up to set email alerts
|

Keratins regulate Hsp70-mediated nuclear localization of p38 mitogen-activated protein kinase

Abstract: Intermediate filament protein keratin 8 (K8) binds to heat shock protein 70 (Hsp70) and p38 MAPK, and is phosphorylated at Ser74 by p38α (MAPK14, hereafter p38). However, a p38 binding site on K8 and the molecular mechanism of K8-p38 interaction related to Hsp70 are unknown. Here, we identify a p38 docking site on K8 (Arg148/149 and Leu159/161) that is highly conserved in other intermediate filaments. A docking-deficient K8 mutation caused increased p38-Hsp70 interaction and enhanced p38 nuclear localization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…However, this localization seems to occur in only a limited number of systems, whereas, in most cases, p38α/β are localized in the cytoplasm of resting cells. As for the mechanisms that regulate the dynamic subcellular localization, similarly to ERKs [ 109 ], it was shown that the cytoplasmic localization of p38α/β is mediated by various cytoplasmic anchoring proteins such as PTP-SL [ 106 ], keratins [ 110 ], and others [ 111 ]. Upon stimulation, the p38α/β detach from their anchors by mechanisms that may [ 112 ] or may not [ 113 ] require the activating TGY phosphorylation.…”
Section: Subcellular Localization Of P38α/β and Their Substratesmentioning
confidence: 99%
“…However, this localization seems to occur in only a limited number of systems, whereas, in most cases, p38α/β are localized in the cytoplasm of resting cells. As for the mechanisms that regulate the dynamic subcellular localization, similarly to ERKs [ 109 ], it was shown that the cytoplasmic localization of p38α/β is mediated by various cytoplasmic anchoring proteins such as PTP-SL [ 106 ], keratins [ 110 ], and others [ 111 ]. Upon stimulation, the p38α/β detach from their anchors by mechanisms that may [ 112 ] or may not [ 113 ] require the activating TGY phosphorylation.…”
Section: Subcellular Localization Of P38α/β and Their Substratesmentioning
confidence: 99%
“…To evaluate whether PKG is the kinase responsible for T37 phosphorylation, we first investigated the interaction between M1 and PKG. PKG was easily detected in the precipitates of M1-37A but was less readily detected in those of M1-37T ( Fig 4B ), suggesting that the binding of PKG with its substrate, M1-37T, was transient, as are many kinase–substrate interactions [ 27 29 ]. We then performed an in vitro kinase assay, which is recognized as the most direct approach for verifying the substrate of a kinase [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of nuclear p38 in regulating gene expression has prompted extensive research on the molecular mechanisms of its nuclear shuttling. Increasing evidence demonstrated that p38 is localized in the cytoplasm of resting cells due to interactions with various anchoring proteins such as phosphatases PTP-SL [ 38 ], keratins [ 23 ], and others [ 39 ]. Upon stimulation, most p38 molecules detach from their cytoplasmic anchors and rapidly translocate into the nucleus via the nuclear pore [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stimulated nuclear translocation of p38 is likely to be regulated by a unique shuttle mechanism. Actually, several pivotal studies have reported that HSP70 [ 22 , 23 ], SUMO-2 [ 24 ], as well as three β-like importins, importin 3, 7, and 9 [ 25 ] interact with p38 in response to certain stimuli, and escort the kinase into the nucleus. However, the specific protein/protein complex and the mechanisms by which these components are involved in p38 translocation in response to mechanical stretch are not clear.…”
Section: Introductionmentioning
confidence: 99%